PROFESSIONAL SKILLS IMPROVEMENT MEASURES IN ADDITIONAL PHYSICAL EDUCATION SYSTEM - Shavkat Abdurakhmonov (Journal Park Publishing, 2023)
The process of physical education is multifaceted. In this process, both education and training are provided. In the process of physical education, education is aimed at forming and improving movement skills and competencies. At the same time, the physical development of the participants is affected. The unity of all types of education, their mutual influence is one of the basic pedagogical laws. Currently, our transition to market relations requires a completely new approach to the organization and implementation of the process of professional development of specialists in all aspects of production. Also, in the National Program of Personnel Training, a lot of attention is paid to this issue. Currently, the problem of developing the professional skills of specialists in the theory and practice of physical education is one of the main problems related to professional development.
Keywords: sports, physical education, professional skills, physical culture, healthy lifestyle.